Antibody responses to a highly conserved peptide in HCV E2 protein correlate with chronicity or spontaneous clearance of HCV infection - Yong He; Lilin Zhong; Anthony Ruvindi DeSilva; Kam Sang Kwok; Lu Deng; Maria Luisa Virata; Hailing Yan; Dorothy Scott; Marian Major; Harvey J. Alter; Pei Zhang (Proceedings of the National Academy of Sciences, 2026)
Hepatitis C virus (HCV) infection frequently progresses to chronicity rather than spontaneous clearance, resulting in severe liver diseases including cirrhosis and hepatocellular carcinoma. The molecular mechanisms governing infection outcomes remain poorly understood. We identified Peptide A, a highly conserved epitope (residues 442 to 451) within HCV glycoprotein E2, and demonstrated that differential antibody binding patterns to this region correlate with distinct infection outcomes. This immunogenic, nonneutralizing epitope localizes to a structurally exposed region that shares residue 442 as a boundary with the previously characterized Epitope II (residues 430 to 442) and is positioned adjacent to variable region 2 (VR2, residues 460 to 485). Antibodies requiring both F442 and F447 residues within Peptide A for binding emerged early following infection and demonstrated strong correlation with chronic HCV progression. In contrast, antibodies binding exclusively to F447 were associated with spontaneous viral clearance and consistently co-occurred with Epitope II antibodies during later phases of infection. By establishing the relationship between these distinct antibody binding patterns and divergent infection outcomes, our findings elucidate potential HCV immune evasion mechanisms and may facilitate the development of predictive tools for determining chronic versus clearance outcomes early in infection, as well as inform rational vaccine design strategies.